Public Perception Of The Oil Palm Company Pt. Bumi Sawindo Permai And Its Relationship With The Economic Welfare Of The People Of Tanjung Lalang Village Tanjung Agung District Muara Enim Regency - Kinanti, Harda; Sriati, Sriati (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2023)
Perception is a form of response that occurs in individuals obtained from the results of interpretation of themselves and their environment. Everyone has a tendency to see the same thing in different ways. Public perception of palm oil company PT. Bumi Sawindo Permai and its relationship with community welfare in Tanjung Lalang Village, Tanjung Agung District, Muara Enim Regency, the community has different perceptions, therefore the objectives of this study are (1) To measure public perceptions of palm oil companies PT. Bumi Sawindo Permai in Tanjung Lalang Village, Tanjung Agung District, Muara Enim Regency (2) To analyze the income and welfare of people living around the palm oil company PT. Bumi Sawindo Permai (3) to analyze the relationship between public perception of palm oil company PT. Bumi Sawindo Permai with community welfare in Tanjung Lalang Village, Tanjung Agung District, Muara Enim Regency. This research was conducted in Tanjung Lalang Village, Tanjung Agung District, Muara Enim Regency in March 2023 The research method used is the survey method and the sampling method is the simple random sample method. The data used are primary data and secondary data. The results of this study are: (1) Public perception of palm oil companies seen from perceptions of the environment, health, infrastructure, education, and income in Tanjung Lalang Village, Tanjung Agung District, Muara Enim Regency with an average of 41.17 included in the approval criteria. (2) The average income of the people in Tanjung Lalang Village, Tanjung Agung District is Rp. 361,286,521 / Th and the level of welfare in Tanjung Lalang Village is classified as high level of welfare (3) The relationship between people's perception of well-being has a strong correlation of 0.679 and a significant relationship because the significant value of 0.000<0.05 means that the correlation between perception and well-being has a strong relationship.